Cloning and expression in Saccharomyces cerevisiae of a Trichoderma reesei beta-mannanase gene containing a cellulose binding domain. - Stålbrand, H (1995)
beta-Mannanase (endo-1,4-beta-mannanase; mannan endo-1,4-beta-mannosidase; EC 3.2.1.78) catalyzes endo-wise hydrolysis of the backbone of mannan and heteromannans, including hemicellulose polysaccharides, which are among the major components of plant cell walls. The gene man1, which encodes beta-mannanase, of the filamentous fungus Trichoderma reesei was isolated from an expression library by using antiserum raised towards the earlier-purified beta-mannanase protein. The deduced beta-mannanase consists of 410 amino acids. On the basis of hydrophobic cluster analysis, the beta-mannanase was assigned to family 5 of glycosyl hydrolases (cellulase family A). The C terminus of the beta-mannanase has strong amino acid sequence similarity to the cellulose binding domains of fungal cellulases and is preceded by a serine-, threonine-, and proline-rich region. Consequently, the beta-mannanase is probably organized similarly to the T. reesei cellulases, having a catalytic core domain separated from the substrate-binding domain by an O-glycosylated linker. Active beta-mannanase was expressed and secreted by using the yeast Saccharomyces cerevisiae as the host. The results indicate that the man1 gene encodes the two beta-mannanases with different isoelectric points (pIs 4.6 and 5.4) purified earlier from T. reesei.